Experiences of healthcare providers of older adults with cancer during the COVID-19 pandemic. Issue 2 (March 2021) - Krok-Schoen, Jessica L.; Pisegna, Janell L.; BrintzenhofeSzoc, Karlynn; MacKenzie, Amy R.; Canin, Beverly; Plotkin, Elana; Boehmer, Leigh M.; Shahrokni, Armin
Abstract: Objectives: Care for older adults with cancer became more challenging during the COVID-19 pandemic. We sought to examine healthcare providers' clinical barriers, patient questions, and overall experiences related to care delivery for these patients during the pandemic. Materials and methods: Members of the Advocacy Committee of the Cancer and Aging Research Group along with the Association of Community Cancer Centers developed a 20-question survey for healthcare providers of older adults with cancer. Eligible participants were recruited by email sent through professional organizations' listservs, email blasts, and social media. This manuscript reports the qualitative data from the survey's three open-ended questions. Free text, open-ended survey items were analyzed by two independent coders for identification of common themes using NVivo software. Theme agreement was reached through consensus and count comparisons of participant responses were made. Results: Healthcare system organizational challenges and meeting basic needs and support were commonly reported themes among respondents ( n  = 274). Barriers to care delivery included organizational challenges, patients' access to resources and support, concerns for patients' mental and physical health, and telehealth challenges. Respondents reported older adults were asking about their health and cancer care as well as access to basic needs and supports. Providers described worrying about patients' mental health, fear of personal safety, frustration in multi-level institutions, as well as experiencing positive leadership and communication. Conclusion: Providers are faced with balancing their concerns for personal and patient safety. These findings demand resources and support allocation for older adults with cancer and healthcare providers during the COVID-19 pandemic.